Transforming Society through Creative Technology: Case Studies of Social Innovation in Game Design and Virtual Reality - Xu, Shanshan; Jixiong, Cai; Wei, Zhang (Yayasan Adra Karima Hubbi, 2024)
The advent of creative technologies such as game design and virtual reality (VR) has opened new avenues for social innovation. These technologies offer immersive and interactive experiences that can address various societal challenges, from education to mental health. Despite their potential, there is limited comprehensive research on how these technologies are being utilized in social innovation. This research aims to explore how creative technologies in game design and virtual reality are transforming society through social innovation. The study seeks to identify successful case studies and analyze the impact of these technologies on different social sectors. The research employs a qualitative case study approach, examining six social innovation projects that leverage game design and VR. Data were collected through in-depth interviews with project leaders, direct observation, and analysis of project outcomes. This approach provides a detailed understanding of the implementation processes, challenges, and successes of each project. The findings indicate that game design and VR have significant potential to create positive social change. Projects in education showed enhanced student engagement and learning outcomes, while mental health initiatives reported improved therapeutic experiences and patient well-being. Other projects addressed issues such as social inclusion and environmental awareness, demonstrating the versatility and effectiveness of these technologies. The study concludes that creative technologies in game design and VR can play a transformative role in social innovation. By providing engaging and immersive experiences, these technologies can effectively address a wide range of societal challenges. Continued research and investment in these areas are recommended to fully harness their potential for social good.